Analysis of the Characteristics and Psychological Characteristics of Athletes’ Illegal and Criminal Behaviours - Shangeng Shi; Qiusheng Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to study the characteristics and psychological characteristics of athletes' illegal and criminal behaviours, this paper puts forward a study on the disciplinary violations of High-performance sport athletes in China. This study used the methods of literature review and expert interviews to analyze the disciplinary violations of High-performance sport athletes in China. The results show that the disciplinary violations of High-performance sport athletes in China mainly include match fixing, false age, false gender, doping, violence, etc. The reasons for these disciplinary violations involve low education level, distorted ideological concepts, weak legal awareness, inadequate sports laws and regulations, and the impact of social misconduct. In response to the existing problems, some feasible suggestions have been put forward, including strengthening the construction of athletes' moral quality, strengthening the cultivation of legal awareness, strengthening the construction of sports legal system, and increasing the punishment for disciplinary violations. These suggestions are intended to lay a foundation for the rapid, stable, civilized and healthy development of High-performance sport in China. In summary, in order to solve the problem of illegal and criminal behaviour among athletes, it is necessary to play the guiding role of the Sports Law and improve the legal responsibility for doping violations; Expand the application of civil compensation, broaden the channels for athletes' relief, and encourage athletes to request compensation for infringement liability; Improve relevant administrative regulations and provide guarantees for inspections outside doping competitions; Strictly crack down on doping crimes and use criminal punishment to crack down on the doping crime circle. These measures will help solve the problem of athletes' crimes and promote the healthy development of High-performance sport.